Unlocking Relief: A Comprehensive Study For a Safer And Earlier Recovery By Microscopic Fenestration And Discectomy For PLID (East West Medical College Journal, 2026)
Background: Prolapsed Intervertebral Disc (PLID) occurs when the nucleus pulposus herniates through the annulus fibrosus and compresses neural structures, resulting in pain, sensory disturbances, and motor weakness. Microscopic fenestration and discectomy has emerged as a minimally invasive and effective surgical option for lumbar disc prolapse.Objective: To evaluate the clinical outcome, safety, recurrence, and postoperative complications of microscopic fenestration and discectomy in patients with PLID.Methods: This prospective observational study was conducted at Zainul Haque Sikder Women’s Medical College & Hospital (ZHSWMCH), Dhanmondi, Dhaka, from January 2024 to December 2024. A total of 64 patients aged 18–70 years with single or double level lumbar PLID were included. Preoperative diagnosis was confirmed by MRI. All patients underwent microscopic fenestration and discectomy under aseptic precautions by a single surgeon. Patients were followed up postoperatively for two weeks. Clinical outcomes were assessed through motor and sensory improvement, PROLO scale evaluation, and postoperative complications.Results: Among the 64 patients, the majority belonged to the 41–60 years age group (43.75%). The most common level of disc prolapse was L4–L5 (71.8%), followed by L5–S1 (15.6%). Posterolateral left-sided prolapse was the most frequent presentation (40.6%). Preoperatively, extensor hallucis longus weakness was present in 43.7% patients, which reduced to 4.6% postoperatively. Sensory deficit at the L5 level was most common preoperatively (42.1%), while 57.1% patients had no sensory deficit postoperatively.Functional improvement assessed by the PROLO scale demonstrated marked postoperative recovery, with 47 patients categorized in E1 status after surgery compared to 13 preoperatively. Postoperative complications were minimal, with recurrence at the samelevel in only 2 patients and bladder-bowel complication in 1 patient.Outcome: Microscopic fenestration and discectomy resulted in significant improvement in motor and sensory function, early mobilization, reduction in pain, better rehabilitation outcomes, and fewer postoperative complications. The procedure also proved cost-effective with reduced analgesic requirements and fewer follow-up visits. Conclusion: Microscopic fenestration and discectomy is a safe, effective, and reliable surgical technique for the management of PLID. The procedure provides satisfactory functional recovery with minimal recurrence and complications, making it an appropriatesurgical option for selected patients in resource-limited settings.EWMCJ Vol. 14, No. 2, July 2026: 197-201